ESG performance and firm value: what matters most for investors in Indonesia? - Hamidi, Muh. Isnaini; Utama, Anak Agung Gede Satia (Jurnal Akademi Akuntansi, 2026)
Purpose: Rising awareness of social and environmental responsibility has garnered increasing attention from investors and regulators, especially following recent financial, social, and environmental crises. This study examines the impact of Environmental, Social, and Governance (ESG) factors on firm value, measured by Tobin's Q, to assess how various ESG components influence companies' market value. Methodology/approach:  We use ESG data from Bloomberg and employ quantitative analysis to assess the relationship between ESG scores both overall and in individual components (Environmental, Social, and Governance) and firm value. Findings:  Overall ESG score, along with social and governance components, significantly positively impacts firm value. However, the environmental score doesn’t have a significant effect. These findings suggest that while environmental performance matters, the market in Indonesia has yet to fully recognize its value. Practical and Theoritical contribution/Originality: This research contributes to the growing literature on ESG by focusing on the Indonesian market and demonstrating that social and governance dimensions are more highly valued than environmental performance in influencing firm value. Research Limitation:  The ESG data from Bloomberg for 2024 is limited, which affects the accuracy of the results interpretation. Future research should examine how factors like macroeconomic policies and political conditions influence this relationship.